"The Island of Thieves": Rethinking Empire and the United States in Micronesia. Issue 1 (29th September 2017) - Alessio, Dominic; Renfro, Wesley B
Abstract: This piece examines empire by purchase and lease in the Pacific and the manner by which the United States gained control over a series of strategically valuable islands in the region. Because Washington obtained its possessions partly through purchase and lease, and not via invasion, it argues that the United States can hide its standing as an empire. Therefore, this research suggests that the literature on empire, order, and hierarchy in international relations needs to allow for a more expansive definition of empire to better understand this important but understudied concept.